DECISION CONCEPTS - Sirola, Miki (International Journal of Computing, 2014)
Decision making is done in many application areas. Still most studies are done in such fields as economy and production planning. In methodologies used there exists more variation. This paper reviews the decision concepts discussed in the literature. Also some decision models by the author are commented. The field and practise in decision science is summarized. Although decision support systems are the final results of many projects, they are mostly based on the decision concepts behind the studies that deserve also more detailed examination. Decision analysis approach and knowledge-based technologies are examples of commonly used concepts.